Initiation of ivabradine in cardiogenic shock. (23rd July 2019) - Chiu, Michael H.; Howlett, Jonathan G.; Sharma, Nakul C.
Abstract: Aims: Ivabradine is a selective sinus node inhibitor indicated in patients with symptomatic chronic heart failure on stable guideline‐recommended heart failure therapy including appropriate doses of beta‐blockers. The use in cardiogenic shock remains off label and has been considered a contraindication due to the theoretical risk of attenuating compensatory tachycardia. Tachycardia, especially in the context of inotropic therapy, may be deleterious, resulting in increased myocardial oxygen consumption and reduction in diastolic filling. As ivabradine does not have negative inotropic action, it may present a potential means to manage tachycardia in cardiogenic shock. We present a case series of four patients with cardiogenic shock started on ivabradine who were unable to tolerate beta‐blockers. Methods and results: Five patients identified with cardiogenic shock defined as a severe reduction in cardiac index (<2.0 L/min/m 2 ) and elevated filling pressures on inotropic therapy were started on ivabradine in patients with sinus tachycardia [heart rate (HR) >100] who were intolerant to beta‐blockers. Each patient had a cardiac magnetic resonance imaging, echocardiogram, and coronary angiogram for determination of aetiology. Invasive haemodynamics via pulmonary artery catheterization were measured during initiation and titration of ivabradine (baseline, 6, 12, 24, and 48 h after ivabradine administration) with continuous telemetry monitoring for any dysrhythmia or bradyarrhythmias. All patients tolerated ivabradine initiation, and at 24 h, an observed decrease in HR (106 ± 6.8 vs. 91.6 ± 6.4 b.p.m., P  = 0.04), pulmonary arterial occlusion pressure (30.4 ± 4.8 vs. 24 ± 5.1 mmHg, P  = 0.04), and right atrial pressure (16.8 ± 6.2 vs. 9 ± 4.3 mmHg, P  = 0.0002). An improvement was observed in mixed venous oxygen saturation (SvO2 ) (51 ± 8.8 vs. 64.8 ± 5.3%, P  < 0.04), stroke volume (37.2 ± 7.6 vs. 49.2 ± 12.9 mL, P  < 0.04), and right and left ventricular stroke work index ( Table 1 ). No significant changes were observed with mean arterial pressure (73.4 ± 7.5 vs. 75.8 ± 5.0 mmHg, P  = 0.81) and thermodilution‐derived cardiac index (1.7 ± 0.2 vs. 2.5 ± 0.7 L/min/m 2, P  = 0.58). Inotropic support was weaned successfully in three of five patients (88 ± 30 h) with subsequent titration of beta‐blocker therapy. Two patients improved clinically but ultimately required left ventricular assist device implantation. All patients were discharged alive from hospital at 17 ± 7.9 days following ivabradine initiation. Conclusions: In our small non‐randomized series of patients in cardiogenic shock, ivabradine was safely used to reduce HR in patients previously intolerant of beta‐blockade. There are limited data surrounding the use of ivabradine in cardiogenic shock, and future studies should be undertaken to determine the optimal HR in humans with cardiogenic shock and whether systematic limitation of peak HR may improve outcomes.